Study on Victimology of Abortion on Pregnant Women who do not Get the Husband’s Approval - Sutarno Hardjodirjo; Dewi Setyowati (Hang Tuah Law Journal, 2019)
Observing Article 71 and 72 of Law Number 36 Year 2009 on Health, it can be concluded that every pregnant woman who has fulfilled the legal requirements for the benefit of the pregnant woman to have an abortion can not be intervened by a legitimate partner. Indonesian Government Regulation Number 61 Year 2014 on Reproductive Health, which is an implementing regulation Health Act above, Article 26 Paragraph 1 explained that every woman has the right to undergo a healthy sexual life safely, without coercion and discrimination, without fear, shame, and guilt. One explanation healthy sexual life in verse two is free from physical and mental violence. The problem that arises is when a woman is medically to be aborted for the safety of the woman and meets all requirements of an abortion but did not get the approval of her husband because of certain reasons. Based on the principle of legal certainty, abortion would not be able to do as opposed to legislation by not getting the husband's consent, whereas if the terms of the principles of justice and expediency, a woman has the right to get her human rights, the right to live and determine her own destiny.